Regioselective synthesis of 1,4,5-trisubstituted 1,2,3-triazole derivatives from alpha,beta-unsaturated carbonyls - Verma, Naimish K.; Bera, Smritilekha; Gonnade, Rajesh; Mondal, Dhananjoy (European Journal of Organic Chemistry, 2022)
The copper-catalyzed oxidative azide-olefin cycloaddition (OAOC) reaction of differently substituted alpha,beta-unsaturated carbonyls with azides provided an efficient method for preparing biologically active 1,4,5-trisubstituted 1,2,3-triazoles. In this study, the cycloaddition reaction was found to be a simple and powerful method for constructing diverse mono- and bis-(1,4,5-trisubstituted 1,2,3-triazole) functionalized heterocyclic compounds in moderate to high yields with great regioselectivity. The XRD-analysis data of one of the bis-triazole derivatives supported the regioselectivity as well as the conformity of the method in the construction of the triazole nucleus. The preliminary antifungal profile against C. albicans was observed with cinnamaldehyde-based triazole derivatives demonstrating promising results.
Keywords: alpha; antifungal; beta-Unsaturated carbonyls; Cycloaddition; Dibenzalacetone; Triazole